Patriarchy and Oppression in Sylvia Plath’s Lady Lazarus - Karo, Hasan H. (Humanities Journal of University of Zakho, 2024)
This paper discusses Sylvia Plath’s feelings towards her patriarchal society. In her poem, Lady Lazarus, she expresses her contempt for the mistreatment she receives from the close male members of her family, her father, and husband. Through the poetic lines in the poem, she illustrates the world that women live within a patriarchal society. This paper justifies her hatred of men that Plath conveys in her poem. Her poetic lines in Lady Lazarus are analyzed to show her inner feelings. The paper also explains Plath’s attitude against this oppression that she suffers from. It explains how Plath employs an example of oppression to blame patriarchy for their actions.